An assessment of environmental flow requirements of Indian river basins - Smakhtin, Vladimir U.; Anputhas, Markandu (International Water Management Institute, 2006)
The primary purpose of this report is to stimulate the debate about environmental water allocations in India, where this concept is only beginning to receive attention and recognition. It is a component of a larger research project which aims to assess multiple aspects of India's National River Linking Project and water future in general.